Um estudo autoetnográfico em aulas de língua inglesa no ensino médio: reflexões sobre (de)colonialidades, prática docente e letramento crítico - Bezerra, Selma Silva (2019)
This thesis aims at understanding how the research process triggered reflections in my views and practices of teaching, while I taught English Language to a first year high school group at Federal Institute of Alagoas, Campus Satuba. The research lies in the field of Applied Linguistics, which views language from a dialogic view, one inserted in social practices. It is based on theoretical assumptions of the Decoloniality/Modernity group that criticizes Eurocentric parameters of Latin American ways of life and, as a consequence, advocate ways of knowledge production apart from those parameters. This theory pursues another social order,searching epistemological principles that can contribute to a theoretical and practical confront to the effects of coloniality. Those postulates help to see that the English Language classroom also underwent coloniality consequences, since it works with textbooks and methods produced in colonizer countries. The theoretical support is also based on the concept of critical literacy from Janks (2010; 2012; 2016), understood as an exercise of critical language appropriation; Monte Mór (2012), comprehended as breaking the interpretative circle and expansion of perspectives; and Mclaughlin e De Voogd (2004), as an intervention practice, that comes from the study of the word as a means to intervening in the world. The methodology applied is autoethonography (ELLIS; ADAMS; JONES, 2015, 2013), because it advocates individual stories in order to construct/expand theories and the respect to cultural identities of the participants involved in the process. It is a narrative of an investigation process, with description and interpretation of my steps and choices in a high school group, as well as the productions and speeches of my students. My teaching practice investigated in the study allowed a critical work with five subjects chosen by students, such as: notions of love, problems faced by women, immigration, environment protection and English language history. As a result, I noticed many moments that trigged reflections and reconstructions of my teaching practice, such as: students’ participation in classroom procedures, the relationship with the group in and outside the pedagogical space, and the development of an effort of awareness and social action. In students’ observations critical and reflective thoughts related to women visibility in the society, as well as social prejudice and the need of a conscious action in the world were identified. Also, speeches that lead to the effects of coloniality in the students talks and in the classroom practices of the teacher, the author of this thesis were questioned.